Phosphorylations: making the Neurospora crassa circadian clock tick - Diernfellner, Axel; Schafmeier, Tobias (FEBS letters, 2011)
Various post-translational modifications have been identified that play a role in the function of circadian clocks. Among these, phosphorylation has been investigated extensively. It was shown that phosphorylation influences half-life, subcellular localisation, transcriptional activity and conformation of clock components over the course of a circadian day. Recent observations also indicate that time-of-day specific sequential phosphorylation of the Neurospora crassa clock protein FREQUENCY is crucial for measuring time and thus for establishing a robust circadian rhythm. The circadian clock of Neurospora is one of the best-investigated molecular clocks to date. In this review, we summarise the data on what is known so far about the role of phosphorylation of proteins involved in the Neurospora circadian clock.